FAKTOR YANG MEMPENGARUHI KEPEMILIKAN JAMBAN PADA MASYARAKAT DI LINGKUNGAN VI KELURAHAN BAGAN DELI KECAMATAN MEDAN BELAWAN - Silalahi, Novrika; Malau, Pitto Pratiwi; Sahliza, Sahliza (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
Environment VI is one of the neighborhoods in Bagan Deli Village, Medan Belawan District. Based on a preliminary survey conducted in the Neighborhood in Bagan Deli Village, Medan Belawan it is known that the percentage of household heads who do not have latrines is 53 respondents 77.9%, and respondents who have latrines are 15 respondents 22.1%.This study aims to analyze the relationship between individual characteristics and social support with latrine ownership in the community in Environment VI, Bagan Deli Village, Medan Belawan District. This type of analytic research with cross sectional design, using data primary data obtained from respondents, namely the Head of the Family with the instrument questionnaires and secondary data obtained from the Bagan Deli village office. The data were analyzed analytically and statistically tested with the Chi Square test at the 95% confidence level. The results of statistical analysis show that there is a significant relationship between knowledge and ownership of latrines in the community (p = 0.000), education and ownership of latrines in the community (p = 0.001), occupations with latrine ownership in the community (p = 0.067), income with latrine ownership in the community (p = 0.000), and social support with ownership of latrines in the community (p=0.000). The conclusion of this study is that there is a significant relationship. Between knowledge, education, income, and social support with the ownership of latrines in the community in Environment VI, Bagan Deli Village, Medan Belawan District. It is recommended for health workers in the working area of ​​the Puskesmas and support from various parties in Environment VI, Bagan Deli Village, Medan Belawan District to provide continuous health education regarding the importance of latrine ownership and environmental sanitation and it is hoped that the government will build latrine public (communal latrine) as a means/place to defecate for people who have not been able to build latrines in the community, especially in Environment VI, Bagan Deli Village, Medan Belawan District.